Strategi Pengembangan Produk pada Startup Trafeeka Coffee dengan Penambahan Rempah sebagai Variasi Rasa - Divia Ramadina Hazzelia; Dwi Purnomo (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2021)
Kopi Susu Rempah, an innovative product of startup named Trafeeka Coffee, is expected to increase the market by doing an exact product development strategy. This research aims to create the formula of the product that is preffered by customers. The method in the research used descriptive method, while the data analysis used qualitative analysis. The primary data were obtained through in-depth interviews. Stages of research were done by; designed a product development using the lean canvas tool, and the last step is market testing to analyze product acquisition by using a hedonic test. Customers are selected by purposive sampling methods. The validation data were evaluated by Minimum Viable Product (MVP) process by doing three iterations. The purpose implementation of lean canvas was to determined the best product development strategy, which focuses to get comprehensive, valid, reliable and objective data when it applied to the startup business. The results of this study showed a valid and ideal lean canvas design for Kopi Susu Rempah’s product, that delivered the new experience of drinking coffee with a unique taste and aftertaste sensation of herbs based from a highly desireble product formulation, so as to crease sales charts at the final stage.